Spatiotemporal Variability of the Nitrous Oxide Concentrations and Fluxes From a Cascaded Dammed River - Wu, Shengnan; Wang, Xiaofeng; Liu, Tingting; He, Yixin; Que, Ziyi; Wang, Jilong; Li, Hang; Yu, Lele; Zhang, Yuanyuan; Yuan, Xingzhong (Frontiers in Environmental Science, 2021)
Rivers have been largely considered as the source of nitrous oxide (N2O) to the atmosphere. N2O emissions from rivers could be seriously influenced by damming and exhibit unique spatiotemporal patterns in river-reservoir systems. Multiple research studies report N2O emissions from rivers with single reservoirs, but the spatiotemporal patterns and controls of N2O emissions from cascaded river-reservoir system remain unclear. In this study, we investigated the spatiotemporal variations of N2O concentrations and fluxes along a cascade damming river (Wubu River) in Southwest China. Our results showed that N2O concentrations in the Wubu River ranged from 2.5 to 283.2 nmol L−1 with a mean of 50.7 ± 52.3 nmol L−1 and were generally supersaturated with gas fluxes ranging from 11.8 to 805.6 μmol m−2 d−1. N2O concentrations and fluxes showed a significant longitudinal variation with increasing fluxes from upstream to downstream. Meanwhile, for each river-reservoir-released water continuum, local variation of N2O concentrations was also prominent. Reservoir sections and released water sections had 2.7 (1.2–7.9) and 3.4 (1.3–12.2) times higher N2O concentrations than the corresponding upstream river reaches and acted as hotpots for N2O emission. The N2O concentrations had significant correlations with organic carbon, phosphorus, and Chl-a in surface water. Furthermore, the N2O concentrations and fluxes in reservoirs had a significant correlation with hydraulic residence time and hydraulic load, suggesting that fragmentation of hydrologic conditions was an important driver for the spatial variations of N2O concentrations in the Wubu River cascade reservoirs. Our results suggested that hydraulic residence time could predict the variation pattern of N2O fluxes in this small river basin. Seasonal variations of N2O concentrations and fluxes were the highest in autumn and lowest in winter and were mainly attributed to temperature and rainfall. N2O fluxes were much higher in the Wubu River than the average levels of China’s reservoirs and global reservoirs, acting as enhanced N2O emitter. Our study highlighted that the cascade reservoirs not only act as exciters for N2O production and emissions but also form cumulative effects and local hotpots along the longitudinal dimension, which could significantly increase the complexity of the spatiotemporal variability in riverine N2O emissions. Given the increasing construction of new river dams due to growing energy demand, more research should be done to quantify the contribution of cascaded damming to riverine N2O budgets.